Determining youths’ computational thinking skills using confirmatory factor analysis - Muhamad, Mira Qerul Barriah; Doddanavar, Indrajit Ajit; Chowdhury, Shanjida (Institute of Advanced Engineering and Science, 2024)
As technological advancements shape the workforce, computational thinking skills (CTS) are becoming increasingly crucial. The objective of the study is to explore the potential mediating role of professional development and career planning in the association between robotic coding and software and computational thinking. The study selected 308 youths using simple random sampling and the collected data was subjected to structural equation modelling (SEM) and confirmatory factor analysis (CFA) using SmartPLS. Additionally, demographic data were analyzed using statistical package for social sciences (SPSS). The results concluded that the instrument adopted fulfilled the requirements and was valid for measuring CTS. This indicates that the instrument effectively assessed the participants’ proficiency in CTS. The findings of this study have implications for addressing the skills gaps among youths. The outcomes of this research can aid in designing educational interventions and policies that focus on developing computational thinking skills among new graduates. By fostering these skills, youths can better adapt to the demands of the rapidly evolving technological landscape and contribute effectively to the industries and job market influenced by industry 4.0. Further research on longitudinal studies may be beneficial to assess the long-term impact of CTS development initiatives on reducing skills gaps and ensuring youths are equipped for future workforce requirements.